2011
DOI: 10.1038/jp.2011.81
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for maternal outcome in pregnancy complicated with dilated cardiomyopathy

Abstract: Objective: The goal of the study was to determine risk factors for maternal cardiac failure in pregnancy complicated with dilated cardiomyopathy (DCM).Study Design: The subjects were 29 patients diagnosed with DCM before conception or during the first 7 months of pregnancy. DCM was defined as left ventricle end-diastolic dimension (LVDd)X48 mm and/or fractional shortening (%FS)p30% on echocardiography. Patients were followed until at least 1 year after delivery and were categorized into a poor prognosis group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Moreover, Elkayam et al defined 'pregnancyassociated cardiomyopathy' as a condition that was diagnosed during pregnancy (excluding in the last month) and reported similar clinical characteristics to those of PPCM [13]. The former study also showed that pregnancy outcomes were better among women with preexisting DCM than in those with 'pregnancyassociated cardiomyopathy' [6]. Thus, this study focused only on preexisting DCM.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, Elkayam et al defined 'pregnancyassociated cardiomyopathy' as a condition that was diagnosed during pregnancy (excluding in the last month) and reported similar clinical characteristics to those of PPCM [13]. The former study also showed that pregnancy outcomes were better among women with preexisting DCM than in those with 'pregnancyassociated cardiomyopathy' [6]. Thus, this study focused only on preexisting DCM.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies have assessed the outcomes of pregnancies complicated by DCM and the risk factors for cardiovascular events during pregnancy [5][6][7]. However, the influence of medical therapy on pregnancy outcomes and long-term prognosis after pregnancy remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly decreased systolic dysfunction indicated by %FS in HFHS/OP group at late pregnancy and weaning may be attributed to increased left ventricle end-diastolic dimension (LVIDd) or increased posterior wall thickness (LVPWd) 34 . However, decreased %FS was no longer persistent at 6 weeks postpartum which agreed with previous pregnancy studies in mice fed with the standard laboratory chow diet.…”
Section: Discussionmentioning
confidence: 99%
“…Other CM Among the 23 non-ICM/non-PPCM studies reviewed, there were 14 that met the inclusion criteria (353 women; (LVEF reported in 155 (44%)) [41][42][43][44][45][46][47][48][49][50] (online supplemental S51-54). LVEF was <50% in 43 (28%) women and there were 222 (63%) patients assessed for VT/VF and 304 (86%) for maternal death, with VT/VF occurring in 34 (15%) and maternal death in 7 (2%).…”
Section: Peripartum CMmentioning
confidence: 99%